2020
DOI: 10.3390/antiox9020160
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin Reduces Oxidative Stress but Does Not Affect Polyol Pathway in the Lenses of Type 1 Diabetic Rats

Abstract: Prolonged hyperglycemia is one of the main causes of reactive oxygen species and free radicals generation in diabetes which may affect various organs, including the eye. Oxidative damage to proteins and lipids in the eye lens could lead to cataract formation. To cope with oxidative stress, the endogenous antioxidative system may be supported by the supplementation of exogenous antioxidants. The aim of this study was to evaluate the effect of chrysin, a natural flavonoid, on oxidative stress and polyol pathway-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 78 publications
3
11
0
Order By: Relevance
“…Additionally, we observed that treatment of chrysin did not alter the blood glucose level of the diabetic mice, indicating that the treatment of chrysin resulted in an antinociceptive effect, but not related to the anti-diabetic effect. Similarly to our results, Wojnar et al ( 2020 ) suggested that chrysin reveals antioxidative activity in the lenses but shows no antihyperglycemic or antiglycation properties.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, we observed that treatment of chrysin did not alter the blood glucose level of the diabetic mice, indicating that the treatment of chrysin resulted in an antinociceptive effect, but not related to the anti-diabetic effect. Similarly to our results, Wojnar et al ( 2020 ) suggested that chrysin reveals antioxidative activity in the lenses but shows no antihyperglycemic or antiglycation properties.…”
Section: Discussionsupporting
confidence: 92%
“…A decrease in soluble protein levels in the lenses of diabetic animals has been previously reported [ 55 , 84 ]. To the best of our knowledge, there is no available data on the berberine effect on the AOPP level in the lenses or other organs in any experimental model; however, in our previous works we have described that the AOPP level had been reduced in the lenses of diabetic rats treated with different natural substances, such as diosmin, naringenin, chrysin, or resveratrol [ 79 , 80 , 85 , 86 ]. Along with the decrease in the AOPP level after administration of berberine to the diabetic rats, an increase in the soluble protein level in this organ was noted.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned mechanisms, and the fact that the reaction to oxidative stress depends on the cellular context that accompanies this stress and the duration of exposition to ROS, can altogether contribute to different responses of antioxidative enzymes in the lenses of the diabetic animals. Some reports indicate that the activity of enzymes like SOD, CAT, or GPx in the lenses of diabetic animals decreases [ 60 , 62 ], while others demonstrate increases in their activity [ 55 , 84 , 85 ]. This elevated activity of antioxidative enzymes is probably a result of adaptative mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Chrysin is a flavonoid with a 5,7-dihydroxyl structure and is found in honey, propolis, and mushrooms [ 18 ]. Previous studies have pointed out that chrysin has anti-cancer [ 19 ], anti-oxidant [ 20 ], anti-inflammatory [ 21 ], anti-anxiety [ 22 ], and liver-protective effects [ 23 ]. In addition, it was mentioned that, in an adenine-induced chronic kidney disease rat model, the intervention of chrysin had a protective effect on the kidneys by reducing the concentration of serum creatinine (CRE), blood urea nitrogen (BUN), and tumor necrosis factor alpha (TNF-α) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%